Optimizing Last-Mile Delivery and Transportation Modes for the Tempe Supply Chain - Hidayat, Agung Prayudha; Santosa, Sesar Husen; Siskandar, Ridwan; Zahran, Fadhil Rizqi Az; Ananda, Dea; Savanah, Khadijah Meutia; Aisyah, Siti; Putri, Stevani; Nalanaya, Nalanaya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Tempe supply chain is managing the distribution flow of production until it reaches consumers. The distribution flow must be arranged and managed effectively and efficiently to increase the company's productivity and minimize costs. Method is used in this research are Saving Matrix for optimizing route and Break Even Point (BEP) for evaluating the mode Transportation. The research results show that selected route to consumers is obtained via the G-C1-C2-C5-C6-C3-C4-G route with an optimal capacity of 1500 boxes. Meanwhile, an evaluation of the transportation modes owned shows that the company can leaseif the average delivery in one year is below 1000 boxes and has its own mode if deliveries are above 1000 boxes.